Perangkat Lunak Perhitungan Hereditas Pada Tumbuhan - Margaretta, Desi (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2024)
Deadlock Metode codominant marker data is often carried out with the assumption that the marker is dominant, an approach that can oversimplify results and lead to erroneous conclusions. The aim of this paper is to provide a practical guide to conducting codominant data analysis and selecting appropriate software. We provide an overview of the computational methods and basic principles required for statistical analysis of codominant molecular markers to evaluate genetic diversity and molecular characterization of germplasm collections. Each software package is evaluated by analyzing the same set of data. Differences between parameters are detailed, and comments are provided regarding the software output. This paper aims to provide a better understanding of the differences among available software packages, so that researchers can make a choice that suits their codominant genetic analysis needs. spoken in English.